2019
DOI: 10.1126/sciadv.aax7906
|View full text |Cite
|
Sign up to set email alerts
|

Rising CO 2 drives divergence in water use efficiency of evergreen and deciduous plants

Abstract: Intrinsic water use efficiency (iWUE), defined as the ratio of photosynthesis to stomatal conductance, is a key variable in plant physiology and ecology. Yet, how rising atmospheric CO2 concentration affects iWUE at broad species and ecosystem scales is poorly understood. In a field-based study of 244 woody angiosperm species across eight biomes over the past 25 years of increasing atmospheric CO2 (~45 ppm), we show that iWUE in evergreen species has increased more rapidly than in deciduous species. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 54 publications
5
51
0
1
Order By: Relevance
“…5a). The difference between reconstructed Miocene iWUE and that of modern deciduous trees is greater still (deciduous iWUE Q1-Q3 = 27-52), consistent with the expectation that increased Ca favors evergreen trees (Niinemets et al, 2011;Soh et al, https://doi.org/10.5194/cp-2020-30 Preprint. Discussion started: 10 March 2020 c Author(s) 2020.…”
Section: Elevated Co2 and The Early Miocene Biospheresupporting
confidence: 75%
“…5a). The difference between reconstructed Miocene iWUE and that of modern deciduous trees is greater still (deciduous iWUE Q1-Q3 = 27-52), consistent with the expectation that increased Ca favors evergreen trees (Niinemets et al, 2011;Soh et al, https://doi.org/10.5194/cp-2020-30 Preprint. Discussion started: 10 March 2020 c Author(s) 2020.…”
Section: Elevated Co2 and The Early Miocene Biospheresupporting
confidence: 75%
“…Here, t g is the length of the growing season in months, which we can derive from the fossil plant assemblage using the method of Spicer et al (2009). G w , A tot , and iWUE values for Litsea calicarioides, Cryptocarya taieriensis, C. maarensis, cf.…”
Section: Modeling Gas Exchangementioning
confidence: 99%
“…The ESS envelope was determined using deep-sea δ 18 O of benthic foraminifera (Zachos et al, 2001) and the transform function approach from Hansen et al (2013) (Supplement). Proxy-based Neogene C a reconstructions are derived from a previously published compilation (Foster et al, 2017) and are supplemented with more recently published data (Ji et al, 2018;Londoño et al, 2018;Super et al, 2018;Greenop et al, 2019;Moraweck et al, 2019;Steinthorsdottir et al, 2019). Error bars on gas-exchange-based proxy estimates represent ±1σ .…”
Section: Earliest Miocene Comentioning
confidence: 99%
“…Quantitative prediction of iWUE is essential to anticipate plant responses to climate change factors like CO2 and precipitation regime (Adams et al, 2019;Soh et al, 2019). Recent studies have shown an increased need to quantify the rate at which iWUE has been changing in different geographical regions (Adams et al, 2019).…”
Section: Including Mesophyll Conductance In Iwue Estimation Is Criticalmentioning
confidence: 99%
“…The iWUEsim model (Eqn 2) has been widely used to infer iWUE from δ 13 C values in climate archives like herbage (Koehler et al, 2012), tree rings (Frank et al, 2013;van der Sleen et al, 2015), or animal tissues (Barbosa et al, 2010). Compared to instantaneous iWUE derived from gas exchange measurements, biomass-based Δ provides a time-integrated iWUE and enables time-series analysis spanning from days to millennia (Soh et al, 2019;Adams et al, 2020).…”
Section: Introductionmentioning
confidence: 99%